Students’ Perception of YouTube as Authentic Material in Online Learning - Rifari Baron; Sri Arfani; Viviana Lisma Lestari (Jurnal Paedagogy, 2022)
The purpose of the study was to analyze students' perceptions of YouTube as authentic teaching material in online classes. The research method uses qualitative. Participants were taken from the Grammar and Speaking classes as many as 50 students from the English Language Program at Universitas Indraprasta Jakarta. Data were collected using interviews and questionnaires. Data analysis used interactive model analysis form Miles and Huberman that were the stages of data reduction, data display, and concluding. The results show that YouTube can become authentic material if it has content, plot, duration, and originality that suit the needs and learning objectives. Videos on YouTube also have quality and clear sound. However, YouTube is not only assumed to be the main authentic teaching material, but it will be better if it is equipped with journals, websites and books. The results of this study have implications that teachers must know the needs of students regarding teaching materials and videos that are made should be by the level of learning needs